Preparation and Photocatalytic Water Splitting Hydrogen Production of Titanium Dioxide Nanosheets. (5th August 2020) - Li, Fuying; Huang, Yin; Peng, Hongling; Cao, Yu; Niu, Yu
Abstract : Improving the efficiency of photocatalytic water splitting to produce hydrogen is currently a hot topic in research. TiO2 nanosheets are a good carrier of photocatalytic materials and have become attractive materials in the new century because of their high active surface exposure characteristics and special morphology. Considering the advantages and disadvantages of conventional chemical and physical methods that are used for preparing TiO2 nanosheets, an optimized scheme for the preparation of TiO2 nanosheets via hydrothermal calcination was proposed. X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and UV-visible diffuse reflection absorption spectra (DRS) were used to characterize the structure and morphology of the TiO2 nanosheets, and differences in the photocatalytic water splitting hydrogen production activity of the different calcination temperatures were compared. The suitable calcination temperature of the TiO2 nanosheets was 400°C, and the hydrogen production rate was 270 μ mol/h, which indicated that the sheet structure was beneficial for improving the photocatalytic water splitting hydrogen production performance of the material. It is hoped that this work will support the regulation of the surface morphology and surface modification of nanomaterials.